2017
DOI: 10.1002/pip.2901
|View full text |Cite
|
Sign up to set email alerts
|

Industrially feasible, dopant‐free, carrier‐selective contacts for high‐efficiency silicon solar cells

Abstract: Dopant‐free, carrier‐selective contacts (CSCs) on high efficiency silicon solar cells combine ease of deposition with potential optical benefits. Electron‐selective titanium dioxide (TiO2) contacts, one of the most promising dopant‐free CSC technologies, have been successfully implemented into silicon solar cells with an efficiency over 21%. Here, we report further progress of TiO2 contacts for silicon solar cells and present an assessment of their industrial feasibility. With improved TiO2 contact quality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
168
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(169 citation statements)
references
References 32 publications
1
168
0
Order By: Relevance
“…However, by using the TaN x contact, we obtain a device with a higher FF and a comparable www.advenergymat.de www.advancedsciencenews.com V oc , resulting in a slightly higher efficiency than that of singlelayer TiO 2 and TaO x contacts (see Table S1, Supporting Information). [16][17][18]25] These results indicate that the low contact resistivity and moderate surface passivation of the TaN x heterocontact can be maintained on the device. From the HRTEM image of the Si/TaN x /Al interface, shown in Figure 6b, we can also conclude that no interlayer has been formed at the interfaces, and that no intermixing has occurred with either Si or Al, indicating a high stability of the TaN x heterocontact.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…However, by using the TaN x contact, we obtain a device with a higher FF and a comparable www.advenergymat.de www.advancedsciencenews.com V oc , resulting in a slightly higher efficiency than that of singlelayer TiO 2 and TaO x contacts (see Table S1, Supporting Information). [16][17][18]25] These results indicate that the low contact resistivity and moderate surface passivation of the TaN x heterocontact can be maintained on the device. From the HRTEM image of the Si/TaN x /Al interface, shown in Figure 6b, we can also conclude that no interlayer has been formed at the interfaces, and that no intermixing has occurred with either Si or Al, indicating a high stability of the TaN x heterocontact.…”
Section: Resultsmentioning
confidence: 81%
“…[28][29][30][31][32] Metal-oxide, fluoride, and polymerbased DF-CSCs are easy to deposit at an acceptable cost (e.g., thermal evaporation, spin coating, or atomic layer deposition, ALD); however, most of them suffer from a poor stability, either chemically or thermally, [11,16,18,23,24,33] which limits their industrial applications. When the metal is in direct contact with the silicon surfaces, very large densities of electronic states at the interface can be introduced into 8-hydroxyquinolinolato-lithium (Liq), perylene diimide, have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing optical and electrical losses is crucial to increase the power conversion efficiency (PCE) of solar cells; therefore, highly doped regions are aimed to be replaced with dopant‐free carrier selective contacts, that benefit simple deposition methods and less intrinsic losses. Solar cell designs based on dopant free layers, the dopant‐free asymmetric silicon heterostructure (DASH) solar cells, have attained impressive efficiency values exceeding 20% …”
Section: Introductionmentioning
confidence: 99%
“…Solar cell designs based on dopant free layers, the dopant-free asymmetric silicon heterostructure (DASH) solar cells, have attained impressive efficiency values exceeding 20%. 6,7 In order to be used in PV c-Si based cells, TCEs should have high transparency in the 300 to 1200-nm wavelength range, while also having low resistivity to enable large area carrier transport without significant resistive losses. In addition, a good TCE is expected to (a) have compatible work function matching with the adjacent layers to get low contact resistance, 8 (b) be suitable for uniform deposition using conventional methods, (c) enhance the light coupling into the active layer of the solar cell, 9,10 and (d) have a large band gap (>3 eV).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, with a full‐area native SiO x /ALD‐TiO x rear contacts, a PSC SC with efficiency of 20.3% is achieved by Titova and Schmidt . In addition, Yang et al successfully demonstrated the efficiencies of 19.8% and 22.1% in PSC SCs, with a full‐area ALD‐TiO x and thermal‐oxidation SiO x /ALD‐TiO x rear contacts, respectively. As of today, the highest efficiency of TiO x ‐based PSC SCs is achieved by Bullock et al with a remarkable number of 23.1% by a complete Si/TiO x /LiF x /Al contact .…”
Section: Introductionmentioning
confidence: 99%